The use of atherogenic indices as a useful marker to predict cardiovascular risk in patients with spondyloarthritis - Joy, Deepti; Rajamurugan, P. S. Arul; Ramesh, R.; Mythili, S. (International Journal of Advances in Medicine, 2023)
Background: The atherogenic index of plasma (AIP), linked to cholesterol esterification and its correlation with small dense low-density lipoprotein (LDL) levels in the blood, can predict atherosclerosis and coronary heart disease. Methods: The study examined 45 SpA patients from the Institute of Rheumatology, RGGGH, and MMC. They underwent baseline assessments, lipid profiles, measurements, and blood tests. Atherogenic indices (AIP, Castelli’s Risk I and II, atherogenic coefficient) were calculated and defined using thresholds. Results: In this study, most patients were males (68.9%) with a mean age of 37.73. Primary ankylosing spondylitis (AS) was (62.2%), and HLAB27 was positive in 33.3% of cases. Elevated AI was prevalent: AIP>0.11 (51.1%), CR-I>3.5 (males) or >3.0 (females) (77.8%), CR-II>3.0 (26.7%), and AC>3.0 (44.4%). Significant correlations were found between AIP and waist-hip ratio (p=0.045) and AIP and fasting blood sugar [FBS] (p=0.023). High AIP was significantly associated with metabolic syndrome (21.7%) but not high disease activity. CR-I was associated with elevated FBS levels (p=0.033). CR-II was linked to higher uric acid levels (p=0.043) and current TNF inhibitor use (p=0.041), and AC showed no significant associations with the assessed factors. Conclusions: This study underscores AI’s role in assessing cardiovascular risk in spondyloarthritis patients. AIP, CR-I, and CR-II provide vital risk assessment and management insights. AIP effectively identifies metabolic syndrome, while increased Castelli’s risk index II warrants further investigation in a broader population, especially among TNF inhibitor users.